Media and Society:Critical perspectives - Burton,Graeme (Rawat, 2010)
This popular introductory book provides a clear introduction to the key ideas within media studies. The friendly writing style and everyday examples, which made the first edition a favourite with students and lecturers alike, has been retained and updated in this new edition. This comprehensive text provides a wide-ranging perspective on the Media and: — Uses examples and case studies from the real world — Shows how key concepts can help us understand the relationship between the Media and society — Provides a clear explanation of how critical perspectives on the Media construct thinking about media businesses, texts and audiences The fully updated new edition features new boxed summaries of critical approaches and key thinkers. Chapters cover the main topics that students are likely to encounter in their studies, including advertising, media and violence, news, politics, young audiences, globalization, sport, popular music and new technology. This book is essential reading for students in Media Studies, Cultural Studies and courses with a media interest, such as Sociology and English.